A novel solution towards zero waste in dairy farms: A thermodynamic study of an integrated polygeneration approach. (15th February 2021) - Luqman, Muhammad; Al-Ansari, Tareq
Graphical abstract: Highlights: A practical and sustainable solution contributing to zero-waste dairy farming. Integrated utilisation of manure, wastewater and very-low concentration methane. All the wastes are used to fulfil essential requirements of any dairy farms. The system is found stable in varying environmental conditions. The system performance improves at higher ambient temperatures and/or humidity. Abstract: The rising global human population and per capita demands of needed resources in terms of water, energy and food is an increasingly challenging dilemma, which increases in complexity when conceptualised in the context of global climate change. Dairy products are essential foods that are nutritional and contribute towards overall food security. However, ongoing practices in dairy production, and more specifically dairy waste management, are environmentally challenging and hence need to be replaced by more sustainable solutions. From an environmental perspective, the waste output from dairy farms (methane, manure and wastewater) and the demands of energy and clean water are amongst the most substantial. In this regard, a novel approach is presented to address this issue, in which the focus is to utilise maximum wastes to fulfil (or at least reduce) the demands of a dairy farm. Unique to this study, is a proposed polygeneration system that utilises the very low concentration of methane in the barns, and utilises all the dairy farm wastes in an integrated manner. In addition, the system is equipped with a hydrogen cycle which addresses social concerns regarding wastewater reuse for drinking purposes. The proposed system is mainly composed of a combustion chamber, Rankine cycles, NH3 -H2 O Absorption Cooling System, wastewater evaporator, water electrolyser and a fuel cell. A detailed thermodynamic analysis reveals that the system produces 17 MW of electricity, 1350 m 3 /day of clean water, 15.62 kg/s of chilled water and cooling capacity of 9, 256 tons. In addition, the system utilises 864 tons/day of manure, 87.62 tons/day of methane (saving 1950 tons of CO2 equivalent daily) and recycles 793.2 m 3 /day of wastewater. The computed overall energy efficiency of the system is 35.2%, while the overall exergy efficiency is 19.2%. Moreover, the parametric analysis not only demonstrates that the system can perform stably in varying environmental conditions, contrary to other systems, it demonstrates that the system favours harsher hot and humid environments. Ultimately, these results demonstrate that dairy farms in such climates can be operated in a decentralised manner with near zero-emissions and zero-wastes output.